2019
DOI: 10.3390/ijerph17010099
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Anxiety Symptoms among Pediatric In-Patients with Dengue Fever: A Case-Control Study

Abstract: Background: Psychiatric symptoms have been reported in adult patients with dengue fever (DF); however, information on pediatric patients remains inadequate. We sought to identify the prevalence and predictors of depressive and anxiety symptoms and identify other psychiatric symptoms among pediatric patients with DF. This case-control study involved pediatric in-patients (n = 225) who had clinical or serologic-confirmed DF and healthy school-based controls (n = 260). Participants completed the Revised Child Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…19 A case-control study involving pediatric population observed the prevalence of depression (13.3%) and anxiety symptoms (34.2%) during acute dengue infection to be significantly higher than matched controls. 23 Further, around 25% of the admitted children exhibited agitation, aggression, irritability, and visual hallucinations. Delayed psychiatric manifestations of dengue infection were reported to be predominantly depression and anxiety.…”
Section: Psychiatric Manifestationsmentioning
confidence: 98%
See 2 more Smart Citations
“…19 A case-control study involving pediatric population observed the prevalence of depression (13.3%) and anxiety symptoms (34.2%) during acute dengue infection to be significantly higher than matched controls. 23 Further, around 25% of the admitted children exhibited agitation, aggression, irritability, and visual hallucinations. Delayed psychiatric manifestations of dengue infection were reported to be predominantly depression and anxiety.…”
Section: Psychiatric Manifestationsmentioning
confidence: 98%
“…This included 18 case reports, one case series, and eight observational studies. A detailed review of the eight observational studies [16][17][18][19][20][21][22][23] (five cross-sectional, two case-control, and one cohort study) is provided below and summarized in Table 1.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The dengue virus is endemic inIndonesia and Southeast Asia (de Jong et al, 2018). Infection with the dengue virus is associated with depressive symptoms in pediatric patients(Herbuela et al, 2019) and was prevalent among children 1-to 5-years old (between 10% and 20%) during the period we study(Karyanti et al, 2014).7 With respect to increasing the incidence of malaria, the estimated impacts of positive rainfall shocks have positive coefficient but not statistically significant.© 2023 Oxford University and John Wiley & Sons Ltd.…”
mentioning
confidence: 89%
“…Compared to the previous 50 years, the recent global incidence of dengue has climbed to 30-fold [12][13][14], and the unavailability of a safe vaccine is further worsening the menace [15]. The World Health Organization (WHO) estimated ~390 million annual DF infections in 128 countries, placing ~3.9 billion people at risk [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%